Self-myofascial release therapy moderately influence electromyography of longissimus dorsi muscle in golfers - Banaśkiewicz Jan; Kasiak Przemysław; Chomiuk Tomasz; Mamcarz Artur; Śliż Daniel (Sciendo, 2024)
Study aim: The longissimus dorsi (LD) is often injured among golfers. Self-myofascial release (SMFR) therapy is a common injury prevention technique. The purpose of this research was to analyze the impact of SMFR therapy on LD bioelectrical activity among golfers.